Nano three-proofing finishing agent as well as preparation method and application thereof

By using fluorine-containing acrylic emulsion and nano-titanium dioxide powder on silk fabrics, the problem of yellowing of silk fabrics under ultraviolet irradiation is solved, and the multi-functional finishing effect of water, oil and ultraviolet resistance is achieved, improving the performance and environmental protection of the fabrics.

CN119507211APending Publication Date: 2025-02-25SUZHOU EMBROIDERY COLORFUL WORLD EMBROIDERY CRAFT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652207.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Silk fabrics will turn yellow and have a decrease in strength under ultraviolet irradiation. Existing anti-ultraviolet finishing agents are highly irritating to the skin, have poor washing fastness and light stability, and the application of inorganic nanomaterials in textiles is not yet sufficient.

Method used

A tri-preventing finishing agent of fluorine-containing acrylic emulsion and nano-titanium dioxide powder is used to prepare a core-shell structure finishing agent through an emulsification process, and the silk fabric is processed through a two-thick and two-rolling process to form a nano-scale rough surface to improve water-repellent and oil-repellent properties and ultraviolet resistance.

Benefits of technology

The three-proof finishing effect of silk fabrics is achieved, including improving water and oil repellent properties and UV resistance. At the same time, it avoids the adverse impact of conventional perfluoroalkyl chains on the environment and meets the hand feeling requirements of silk fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507211A_ABST
    Figure CN119507211A_ABST
Patent Text Reader

Abstract

The invention relates to a nano three-proofing finishing agent and a preparation method and application thereof.The finishing agent comprises fluorine-containing acrylic emulsion and nano titanium dioxide powder, the fluorine-containing acrylic emulsion is of a core-shell structure comprising a shell structure and a core structure, the shell structure is formed by polymerizing 40-50 wt% of perfluorohexyl ethyl acrylate, 30-40 wt% of 2-ethylhexyl acrylate and an emulsifier, and the core structure is formed by polymerizing 40-50 wt% of perfluorohexyl ethyl acrylate, 30-40 wt% of 2-ethylhexyl acrylate and the emulsifier. The core structure is formed by polymerizing 40 to 50 weight percent of methyl methacrylate, 30 to 40 weight percent of 2-ethylhexyl acrylate and an emulsifier. The finishing agent provided by the invention can realize three-proofing finishing on the real silk fabric, can endow the real silk fabric with anti-ultraviolet performance, and meets the hand feeling requirement of the real silk fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textiles, and in particular to a nano three-proof finishing agent and a preparation method and application thereof. Background Art

[0002] Silk is a natural protein fiber with many excellent wearing properties, such as soft luster, smooth touch, moisture absorption and breathability, lightness and elegance, good drape performance, etc. As an ecological textile, silk fabric is favored by the market. In order to meet the requirements of personalized, novel and functional fabrics, it is imperative to develop multifunctional "three-proof" silk fabrics, which have broad application prospects and economic benefits.

[0003] The triple-proof finishing is to apply a low surface energy finishing agent on the fabric, which firmly adheres to the fiber or forms a chemical bond with it, changes the composition of the fiber surface layer, reduces the surface energy of the fabric, and makes the critical surface tension of the fabric much smaller than the surface tension of liquids such as water or oil. It is no longer wetted by water and oil, making it difficult for water, oil, etc. to spread on the fabric surface, thereby wetting the fabric.

[0004] Although silk fabrics have many excellent properties, they will undergo photo-oxidation reactions under ultraviolet irradiation, causing yellowing and reduced strength. In order to increase the added value of silk fibers and reduce the damage of ultraviolet rays to the human body, silk fabrics must be treated with anti-ultraviolet finishing. Commonly used organic anti-ultraviolet finishing agents are irritating to the skin, have poor wash fastness and poor light stability. Inorganic nanomaterials have the advantages of safety, environmental protection and good stability, and their use in the functional finishing of textiles has become one of the hot topics in the textile field. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a nano three-proof finishing agent and a preparation method and application thereof. The finishing agent can achieve three-proof finishing on silk fabrics and also can impart anti-ultraviolet performance to the silk fabrics.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions: A three-proof finishing agent comprises a fluorine-containing acrylic emulsion and nano titanium dioxide powder. The fluorine-containing acrylic emulsion is a core-shell structure comprising a shell structure and a core structure. The shell structure is polymerized by 40-50wt% of perfluorohexylethyl acrylate, 30-40wt% of isooctyl acrylate and an emulsifier, and the core structure is polymerized by 40-50wt% of methyl methacrylate, 30-40wt% of isooctyl acrylate and an emulsifier.

[0007] Furthermore, the content of the nano titanium dioxide in the finishing agent is 10-20wt%, and the particle size of the nano titanium dioxide is 20-30nm.

[0008] Furthermore, the emulsifier is a polymerizable emulsifier DNS-86, and the amount used is 1 to 3 wt % of the total weight of the monomers.

[0009] Furthermore, the mass ratio of the shell structure to the core structure is 1-2:3-4.

[0010] A method for preparing a three-proof finishing agent, the preparation method comprising the following steps: Step S1: at room temperature, a certain ratio of monomers for shell structure is uniformly stirred at high speed in an aqueous solution with an emulsifier added, and then emulsified at a speed of 8000 to 10000 r / min for 5 to 8 minutes using a high shear dispersing emulsifier to obtain a shell structure monomer emulsion; Step S2: stirring a core structure monomer mixture and nano-titanium dioxide in a certain ratio in a polymerizable emulsifier aqueous solution at high speed to obtain a core structure monomer emulsion; Step S3: taking out 1 / 3 of the core structure monomer emulsion and adding it into a three-necked flask equipped with a constant pressure funnel, a thermometer and nitrogen protection as a seed emulsion, adding a pre-prepared 1 / 3 initiator aqueous solution, slowly stirring evenly in a water bath and heating to 70-75° C., after the system shows blue light at a constant temperature, dripping the remaining core structure monomer emulsion into the system, maintaining a drip rate of 1 drop / s, and after the dripping is completed, adding 1 / 3 of the initiator aqueous solution and reacting at a constant temperature for 20-30 minutes to prepare a core structure emulsion; Step S4: adding the shell monomer emulsion to the core structure emulsion at a rate of 1 drop / 2s at a constant temperature, then heating the system to 75-80°C, adding the remaining 1 / 3 of the initiator aqueous solution, reacting for 40-60 minutes, cooling the prepared emulsion to room temperature, and filtering to obtain the finishing agent emulsion.

[0011] Furthermore, the initiator is potassium persulfate, and the amount used is 1wt% of the total amount of monomers.

[0012] A three-proof finishing agent is used for finishing of silk fabrics. The silk fabrics are treated with 50-60 g / L of the three-proof finishing agent by two dipping and two padding, and then pre-baked and baked at 100-110° C. for 2-3 minutes to obtain the fabric.

[0013] Furthermore, the rolling ratio is 70% to 80%, and the pre-baking is performed at 80 to 90° C. for 2 to 3 minutes.

[0014] The beneficial effects of the present invention are: 1. The present invention adopts perfluorohexyl ethyl acrylate to prepare the silk triple-proof finishing agent, which overcomes the adverse effects of PFOA produced by conventional perfluoroalkyl chains on the environment, and uses short-chain perfluorohexyl ethyl acrylate to avoid the adverse effects of PFOA.

[0015] 2. In the present invention, nano titanium dioxide is added during the preparation of the finishing agent emulsion. The polymer molecular chains in the emulsion prevent the aggregation of nano titanium dioxide powder. When the finishing agent forms a film on the fabric surface, the nano titanium dioxide can form a nano-scale rough surface. The rough surface and the perfluorohexylethyl acrylate fragment synergistically promote the lotus leaf effect, achieving water and oil repellency. At the same time, the nano titanium dioxide improves the anti-ultraviolet performance of the silk fabric.

[0016] 3. The present invention adopts a polymerizable emulsifier to reduce the residual emulsifier after silk fabric finishing. The presence of traditional emulsifiers causes the emulsifier to migrate to the surface of the film during the process of water evaporation and film formation, which greatly affects the water resistance and stain resistance of the film. The present invention meets the hand feel requirements of silk fabrics. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a test diagram of the water contact angle of silk after the nano three-proof finishing agent of the present invention is used to finish the silk. DETAILED DESCRIPTION

[0018] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments.

[0019] The invention provides a three-proof finishing agent, which comprises a fluorine-containing acrylic emulsion and nano titanium dioxide powder. The fluorine-containing acrylic emulsion is a core-shell structure comprising a shell structure and a core structure. The shell structure is polymerized by 40-50wt% of perfluorohexylethyl acrylate, 30-40wt% of isooctyl acrylate and an emulsifier, and the core structure is polymerized by 40-50wt% of methyl methacrylate, 30-40wt% of isooctyl acrylate and an emulsifier.

[0020] The content of the nano titanium dioxide in the finishing agent is 10-20wt%, the particle size of the nano titanium dioxide is 20-30nm, the emulsifier is a polymerizable emulsifier DNS-86, the amount used is 1-3wt% of the total weight of the monomer, and the mass ratio of the shell structure to the core structure is 1-2:3-4.

[0021] The present invention provides a method for preparing a three-proof finishing agent, which comprises the following steps: Step S1: at room temperature, a certain ratio of monomers for shell structure is uniformly stirred at high speed in an aqueous solution with an emulsifier added, and then emulsified at a speed of 8000 to 10000 r / min for 5 to 8 minutes using a high shear dispersing emulsifier to obtain a shell structure monomer emulsion; Step S2: stirring a core structure monomer mixture and nano-titanium dioxide in a certain ratio in a polymerizable emulsifier aqueous solution at high speed to obtain a core structure monomer emulsion; Step S3: taking out 1 / 3 of the core structure monomer emulsion and adding it into a three-necked flask equipped with a constant pressure funnel, a thermometer and nitrogen protection as a seed emulsion, adding a pre-prepared 1 / 3 initiator aqueous solution, slowly stirring evenly in a water bath and heating to 70-75° C., after the system shows blue light at a constant temperature, dripping the remaining core structure monomer emulsion into the system, maintaining a drip rate of 1 drop / s, and after the dripping is completed, adding 1 / 3 of the initiator aqueous solution and reacting at a constant temperature for 20-30 minutes to prepare a core structure emulsion; Step S4: adding the shell monomer emulsion to the core structure emulsion at a rate of 1 drop / 2s at a constant temperature, then heating the system to 75-80°C, adding the remaining 1 / 3 of the initiator aqueous solution, reacting for 40-60 minutes, cooling the prepared emulsion to room temperature, and filtering to obtain the finishing agent emulsion.

[0022] The initiator is potassium persulfate, and the amount used is 1wt% of the total amount of monomers.

[0023] The invention provides a finishing application of a three-proof finishing agent on silk fabrics. The silk fabrics are treated with 50-60 g / L of the three-proof finishing agent by two dipping and two padding, and then pre-baked and baked at 100-110° C. for 2-3 minutes to obtain the finished silk fabrics.

[0024] The rolling rate is 70% to 80%, and the pre-baking is carried out at 80 to 90°C for 2 to 3 minutes.

[0025] The monomer raw materials and nano titanium dioxide used in the three-proof finishing agent of the present invention are all commercially available, as are the initiator and the emulsifier. Unless otherwise specified, all other raw material components are commercially available commodities well known to those skilled in the art.

[0026] The water and oil repellency was tested according to AATCC118-2009 standard. The contact angle test was conducted by CA500S contact angle tester, and the average value was taken after 5 measurements. The durability test was conducted by washing and drying in the standard washing mode of a household fully automatic washing machine, and then the water and oil repellency test was conducted.

[0027] The mechanical stability test method of the emulsion is to run the prepared emulsion on a centrifuge at 2000r / min for 30min and observe the emulsion stratification and precipitation phenomena.

[0028] The emulsion dilution stability test method is to dilute the prepared emulsion with distilled water to a solid content of 4%, seal it and let it stand for 72 hours, and observe the emulsion stratification and precipitation phenomena.

[0029] Example 1 A three-proof finishing agent comprises a fluorine-containing acrylic emulsion and 15wt% of nano titanium dioxide powder (particle size 20nm-30nm), wherein the fluorine-containing acrylic emulsion is a core-shell structure comprising a shell structure and a core structure, wherein the shell structure is polymerized by 45wt% of perfluorohexylethyl acrylate, 30wt% of isooctyl acrylate, and 1wt% of the total monomer mass of a polymerizable emulsifier DNS-86, and the core structure is polymerized by 40wt% of methyl methacrylate, 30wt% of isooctyl acrylate, and 1wt% of the total monomer mass of a polymerizable emulsifier DNS-86; and the mass ratio of the shell structure to the core structure is 1:3.

[0030] The preparation process of the above three-proof finishing agent is as follows: Step S1: at room temperature, a certain ratio of monomers for shell structure is uniformly stirred at high speed in an aqueous solution with an emulsifier added, and then emulsified at a speed of 8000 r / min for 8 minutes using a high shear dispersing emulsifier to obtain a shell structure monomer emulsion; Step S2: stirring a core structure monomer mixture and nano-titanium dioxide in a certain ratio in a polymerizable emulsifier aqueous solution at high speed to obtain a core structure monomer emulsion; Step S3: taking out 1 / 3 of the core structure monomer emulsion and adding it into a three-necked flask equipped with a constant pressure funnel, a thermometer and nitrogen protection as a seed emulsion, adding a pre-prepared 1 / 3 KPS initiator aqueous solution, slowly stirring evenly in a water bath and heating to 70° C., after the system shows blue light at a constant temperature, dripping the remaining core structure monomer emulsion into the system, maintaining a drip rate of 1 drop / s, and after the dripping is completed, adding 1 / 3 of the KPS initiator aqueous solution and reacting at a constant temperature for 25 minutes to prepare a core structure emulsion; Step S4: adding the shell monomer emulsion to the core structure emulsion at a constant temperature at a dripping rate of 1 drop / 2s, then heating the system to 75°C, adding the remaining 1 / 3 KPS initiator aqueous solution, reacting for 45 minutes, cooling the prepared emulsion to room temperature, and filtering to obtain a finishing agent emulsion, wherein the amount of KPS initiator used is 1wt% of the total amount of monomers.

[0031] The prepared three-proof finishing agent has a milky white and delicate appearance, is translucent and has a blue glow, and has very little gel. The mechanical stability, dilution stability and storage stability of the prepared emulsion are relatively stable, and no precipitation occurs after the emulsion is placed for 3 months.

[0032] The finishing process of the above-mentioned three-proof finishing agent when applied to silk fabrics includes the following steps: The silk fabric was treated with the above-mentioned 60g / L three-proof finishing agent by two dipping and two padding, with a rolling rate of 70%, pre-baked at 80℃ for 2min and baked at 110℃ for 2min. Figure 1As shown, the liquid contact angle of the obtained triple-proof finished silk fabric is maintained at about 136°, and the liquid contact angle is still basically maintained above 120° after washing 30 times.

[0033] Example 2 A three-proof finishing agent comprises a fluorine-containing acrylic emulsion and 10wt% of nano titanium dioxide powder (particle size 20-30nm), wherein the fluorine-containing acrylic emulsion is a core-shell structure comprising a shell structure and a core structure, wherein the shell structure is polymerized by 40wt% of perfluorohexylethyl acrylate, 30wt% of isooctyl acrylate, and 1wt% of the total weight of a polymerizable emulsifier DNS-86, and the core structure is polymerized by 45wt% of methyl methacrylate, 35wt% of isooctyl acrylate, and 1wt% of the total weight of a polymerizable emulsifier; and the mass ratio of the shell structure to the core structure is 2:4.

[0034] The preparation process of the above three-proof finishing agent is as follows: Step S1: at room temperature, a certain ratio of monomers for shell structure is uniformly stirred at high speed in an aqueous solution with an emulsifier added, and then emulsified at a speed of 10000 r / min for 5 minutes using a high shear dispersing emulsifier to obtain a shell structure monomer emulsion; Step S2: stirring a core structure monomer mixture and nano titanium dioxide powder in a certain ratio in a polymerizable emulsifier aqueous solution at high speed to obtain a core structure monomer emulsion; Step S3: taking out 1 / 3 of the core structure monomer emulsion and adding it into a three-necked flask equipped with a constant pressure funnel, a thermometer and nitrogen protection as a seed emulsion, adding a pre-prepared 1 / 3 KPS initiator aqueous solution, slowly stirring evenly in a water bath and heating to 75° C., after the system shows blue light at a constant temperature, dripping the remaining core structure monomer emulsion into the system, maintaining a drip rate of 1 drop / s, and after the dripping is completed, adding 1 / 3 of the KPS initiator aqueous solution and reacting at a constant temperature for 20 minutes to prepare a core structure emulsion; Step S4: adding the shell monomer emulsion to the core structure emulsion at a constant temperature at a dripping rate of 1 drop / 2s, then heating the system to 80°C, adding the remaining 1 / 3 KPS initiator aqueous solution, reacting for 40 minutes, cooling the prepared emulsion to room temperature, and filtering to obtain a core-shell finishing agent emulsion, wherein the amount of potassium persulfate KPS initiator used is 1wt% of the total amount of monomers.

[0035] The prepared three-proof finishing agent has a milky white and delicate appearance, is translucent and has a blue glow, and has very little gel. The mechanical stability, dilution stability and storage stability of the emulsion are relatively stable, and no precipitation occurs after the emulsion is placed for 3 months.

[0036] The finishing process of the above-mentioned three-proof finishing agent when applied to silk fabrics includes the following steps: The silk fabric was treated with the above-mentioned 55g / L three-proof finishing agent by double immersion and double rolling, with a rolling rate of 70%, pre-baked at 80°C for 2min and baked at 100°C for 3min. The obtained three-proof finished silk fabric had excellent three-proof properties. The liquid contact angle of the obtained three-proof finished silk fabric was maintained at about 136°, and the liquid contact angle was still maintained above 120° after washing 30 times.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A three-proof finishing agent, characterized in that: The finishing agent comprises fluorine-containing acrylic emulsion and nano titanium dioxide powder. The fluorine-containing acrylic emulsion is a core-shell structure comprising a shell structure and a core structure. The shell structure is polymerized by 40-50wt% of perfluorohexylethyl acrylate, 30-40wt% of isooctyl acrylate and an emulsifier, and the core structure is polymerized by 40-50wt% of methyl methacrylate, 30-40wt% of isooctyl acrylate and an emulsifier.

2. The three-proof finishing agent according to claim 1, characterized in that: The content of the nano titanium dioxide in the finishing agent is 10-20wt%, and the particle size of the nano titanium dioxide is 20-30nm.

3. The three-proof finishing agent according to claim 2, characterized in that: The emulsifier is a polymerizable emulsifier DNS-86, and the amount used is 1 to 3 wt % of the total weight of the monomers.

4. The three-proof finishing agent according to claim 3, characterized in that: The mass ratio of the shell structure to the core structure is 1-2:3-4.

5. A method for preparing the three-proof finishing agent according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step S1: at room temperature, a certain ratio of monomers for shell structure is uniformly stirred at high speed in an aqueous solution with an emulsifier added, and then emulsified at a speed of 8000 to 10000 r / min for 5 to 8 minutes using a high shear dispersing emulsifier to obtain a shell structure monomer emulsion; Step S2: stirring a core structure monomer mixture and nano-titanium dioxide in a certain ratio in a polymerizable emulsifier aqueous solution at high speed to obtain a core structure monomer emulsion; Step S3: taking out 1 / 3 of the core structure monomer emulsion and adding it into a three-necked flask equipped with a constant pressure funnel, a thermometer and nitrogen protection as a seed emulsion, adding a pre-prepared 1 / 3 initiator aqueous solution, slowly stirring evenly in a water bath and heating to 70-75° C., after the system shows blue light at a constant temperature, dripping the remaining core structure monomer emulsion into the system, maintaining a drip rate of 1 drop / s, and after the dripping is completed, adding 1 / 3 of the initiator aqueous solution and reacting at a constant temperature for 20-30 minutes to prepare a core structure emulsion; Step S4: adding the shell monomer emulsion to the core structure emulsion at a rate of 1 drop / 2s at a constant temperature, then heating the system to 75-80°C, adding the remaining 1 / 3 of the initiator aqueous solution, reacting for 40-60 minutes, cooling the prepared emulsion to room temperature, and filtering to obtain the finishing agent emulsion.

6. The preparation method according to claim 5, characterized in that: The initiator is potassium persulfate, and the amount used is 1wt% of the total amount of monomers.

7. An application of the three-proof finishing agent according to any one of claims 1 to 4 or the three-proof finishing agent obtained by the preparation method according to any one of claims 5 to 6 on silk fabrics, characterized in that: The silk fabric is treated with 50-60 g / L of the three-proof finishing agent by double dipping and double padding, and then pre-baked and baked at 100-110° C. for 2-3 minutes to obtain the finished product.

8. The use according to claim 7, characterized in that: The rolling rate is 70% to 80%, and the pre-baking is carried out at 80 to 90°C for 2 to 3 minutes.